Satisfacción laboral y compromiso organizacional en empleados de una universidad privada de Lima - Marquina Vergara, Carlos Francesco (2019)
Job satisfaction and organizational commitment are two constructs that are of great interest to psychologists andespecially for those dedicated to Human Resources. Therefore, this research has investigated both constructs and itscorrelation in private university employees in 2011. We applied the Job Satisfaction Scale SL - SPC (Palma, 1999)and the Scale of Grade of SDA University Employee Commitment (Grajales, 2000) to 121 people belonging to atotal population of 300 individuals who had the employee status. The results reveal that, there is Job dissatisfactionin a 51.3%, where the dimensions: Working Conditions / Materials and Management Policy are issues that causesmayor dissatisfaction among employees; however, and despite of the previous result, the 91.2% have high levelsof organizational commitment, for this reason, they feel identify with and give their loyalty to the Institution. ThePearson correlation between our two variables was 0.73, which is statistically significant (p=0.10) in the studiedpopulation